Cigarette smoking and male lung cancer in an area of very high incidence. II. Report of a general population cohort study in the West of Scotland. Issue 1 (March 1988) - Gillis, C R; Hole, D J; Hawthorne, V M
Abstract : A general population cohort of 7055 men aged 45-64 and resident in Renfrew and Paisley, two urban burghs in the West of Scotland, has been followed for 10 1/2 years. Analysis of the cigarette smoking and lung cancer (incidence and mortality) relation has been undertaken in order to establish whether unusual results found in a case-control study of cigarette smoking and lung cancer in the adjacent city of Glasgow could be confirmed. Lung cancer incidence and mortality rates increased markedly for exposure categories up to an average consumption of 15-24 cigarettes per day. Above this level the rates increased only marginally. Expressing these rates relative to that estimated for the never-smoked group and comparing them with the relative risks estimated in the case-control study revealed a similarity in terms of both the shape and the level of the dose-response relation. Comparison of the lung cancer rates found in this cohort with those observed in other cohort studies in the literature (UK doctors, US Veterans, and American Cancer Society volunteers) suggested that the West of Scotland rates were substantially higher at all levels of cigarette exposure.